Análise das características narrativas e do ambiente digital dos jogos em rede: um estudo de caso do jogo Priston Tale - Molina, William Fernandes (2006)
According to Levy (1999), the new Technologies of the Information and Communication (TIC) are becoming more and more important instruments of our culture and, its use, a concrete way of inclusion and interaction. Murray said (2003, p.17) “The birth of a new media is at the same time stimulant and frightful”, a revolutionary invention as the computer is almost becoming a fascinating history teller. This futurist scene lead us to a necessity of knowing a little bit more about the possibilities that appear each second, investigating its consequences on the human beings. The computer is becoming a powerful representative mean, becoming a new way of media and an indispensable instrument to play games. We observe an accented growth of people that use the computer to play games. The central objective of this research is to investigate and analyze the characteristics of the narratives, the digital environment and the characteristics of hypermedia found in the online games - MMORPG, aiming to study the possibilities of action and participation of the players in the construction of the plot of these narratives. To reach the objective of this work, initially an exploratory research was made, that in such a way aimed to increase the familiarity with the problem, involving this way a bibliographical and theoretical survey on the online games and in the narratives. It was also necessary, the effective participation of the researcher in a MMORPG game, to know, to think, to investigate, to see and to understand the space between lines of the possible narratives of the online games. The game `Priston Tale' was chosen by the author because it allows the participation without any type of payment for the player and it is currently one of the most played game in Brazil. Moreover, it presents as great differential a graphical quality that is not reached by all other games of the type, where the camera modes provides the player 100% of true 3 dimensions experience, approaching each time more the player of the adventure. The research showed that it is possible to construct the plots in the narratives found in the MMORPG, which is a type of online game. However, the options of choice of the players in relation to the type of character, actions and consequently the construction of the narrative plots, are limited by the programming languages used by the developers and inhibit the creation of the authors. Therefore, the suggestion fits a posterior research to study these limitations imposed for the computers and the language of construction of the programs, which finishes influencing in the desistance of the players.